Beliefs von Geschichtslehrpersonen eine Triangulationsstudie - Nitsche, Martin (hep Verlag, 2019)
As a history teacher it is important to acquire a meaningful understanding of what constitutes history, how historical knowledge is developed, and how historical learning and teaching of young people can succeed. Since these assumptions influence history teaching, it is necessary for teachers to reconsider their epistemological concepts and approaches while training to become a history teacher. The present study analyses the effects of teacher training on Swiss-German prospective history teachers' epistemological beliefs, as well as on their assumptions about learning and teaching by applying quantitative methods of survey analysis. The results underline the importance of courses in history and history didactics for the formation of students' concepts. The analysis does, however, also reveals that teacher training in German-speaking Switzerland may also lead to beliefs that are not necessarily defined as goals of higher education in history. Based on survey answers, a qualitative in-depth study with experienced teachers underlines the importance of beliefs for the design of history classes. Furthermore, the use of their assumptions for teaching is also influenced by the pedagogical content knowledge and other concepts (e.g. about learners) of the teachers. On the one hand, the results illustrate the effectiveness of future history teachers' training courses, but on the other hand, they also underpin the need to discuss the design of higher education training for history teachers.